Coverage and educational actions related to the national vitamin A supplementation program: a study in children from the state of Alagoas - Riquelane B.M. Lima; Haroldo S. Ferreira; Andressa L. Cavalcante; Laíse Gabrielly M.L. Santos; Regina Coeli S. Vieira; Monica L. Assunção (Brazilian Society of Pediatrics, 2020)
Objectives: To estimate the coverage of the National Vitamin A Supplementation Program (Programa Nacional de Suplementação de Vitamina A) in children from Alagoas, to identify factors associated with this coverage, and to analyze the adequacy of nutrition education actions. Methods: Household survey involving a representative probabilistic sample of children aged 6 to 59 months from Alagoas and their mothers (n = 509). Coverage was defined by the percentage of children with supplementation records in the last semester. The association between the independent variables (socioeconomic, demographic, and health) and the National Vitamin A Supplementation Program coverage was analyzed based on the prevalence ratio and its 95% CI. The mothers' knowledge of questions related to vitamin A was considered as an indicator of the adequacy of nutrition education actions. Results: Program coverage was 91.9% in children aged 6‐11.9 months and 38.6% in children aged 12‐59 months. In the adjusted analysis, the factors that were associated with greater coverage were: age between 6‐11.9 months (PR = 2.50, 95% CI: 2.10‐2.96), living in rural areas (PR = 1.45, 95% CI: 1.20‐1.76) and living in a house with ≤ 4 rooms (PR = 1.33, 95% CI: 1.09‐1.63). Only 26.1% of the mothers were able to mention some food source of vitamin A and only 19.2% were aware of the consequences of vitamin deficiency for health. Conclusions: The National Vitamin A Supplementation Program coverage is below the targets set by the Ministry of Health (except for children < 12 months). The factors associated with greater coverage indicate an adequate focus of the program. The nutrition education activities have not demonstrated satisfactory results. This information should guide actions to improve the program. Resumo: Objetivos: Estimar a cobertura do Programa Nacional de Suplementação de Vitamina A em crianças de Alagoas, identificar fatores associados a essa cobertura e analisar a adequação das ações de educação nutricional. Métodos: Inquérito domiciliar que envolveu amostra probabilística representativa das crianças de 6 a 59 meses de Alagoas e suas mães (n = 509). A cobertura foi definida pelo percentual de crianças com registro de suplementação no último semestre. A associação entre as variáveis independentes (socioeconômicas, demográficas e de saúde) e a cobertura do Programa Nacional de Suplementação de Vitamina A foi analisada com base na razão de prevalência e seu IC95%. O conhecimento das mães sobre questões relacionadas à vitamina A foi assumido como indicador da adequação das ações de educação nutricional. Resultados: A cobertura do programa foi de 91,9% entre crianças de 6‐11,9 meses e de 38,6% entre as de 12‐59 meses. Na análise ajustada, os fatores que se associaram à maior cobertura foram ter idade entre 6‐11,9 meses (RP = 2,50; IC95%: 2,10‐2,96), residir em zona rural (RP = 1,45; IC95%: 1,20‐1,76) e morar em domicílio com ≤ 4 cômodos (RP = 1,33; IC95%: 1,09‐1,63). Somente 26,1% das mães souberam citar algum alimento fonte de vitamina A e apenas 19,2% conheciam as consequências da deficiência dessa vitamina para a saúde. Conclusões: A cobertura do Programa Nacional de Suplementação de Vitamina A encontra‐se aquém das metas estabelecidas pelo Ministério da Saúde (exceto para crianças < 12 meses). Os fatores associados à maior cobertura evidenciam adequada focalização do programa. As atividades de educação nutricional não ocorrem de forma satisfatória. Essas informações devem nortear ações de aperfeiçoamento do programa. Keywords: Public health, Vitamin A, Supplementation, Health evaluation, Brazil, Palavras‐chave: Saúde pública, Vitamina A, Suplementação, Avaliação em saúde, Brasil